Green synthesized silver nanoparticles for iron and manganese ion removal from aqueous solutions - Moraes, Leonardo C.; Gomes, Marcelo P.; Ribeiro-Andrade, Rodrigo; Garcia, Queila S.; Figueredo, Cleber C. (Environmental pollution (1987), 2023)
Microalgae and Cyanobacteria extracts can be used for the synthesis of spherical silver nanoparticles by the reduction of AgNO3 under air atmosphere at room temperature. Here, we synthesized AgNPs using extracts of one cyanobacterium (Synechococcus elongatus) and two microalgae (Stigeoclonium sp. and Cosmarium punctulatum). The nature of the AgNPs was characterized by TEM, HR-TEM, EDS, and UV–Vis. Considering the large quantity of functional groups in the ligands of AgNPs, we suppose they could retain ion metals, which would be useful for water decontamination. Thus, their capacity to adsorb iron and manganese at concentrations of 1.0, 5.0, and 10.0 mg L−1 in aqueous solutions was evaluated. All experiments were performed in triplicate of microorganism extract with no addition of AgNO3 (control) and AgNP colloid (treatment) at room temperature. The ICP analyses showed that the treatments containing nanoparticles were commonly more efficient at removing Fe3+ and Mn2+ ions than the corresponding controls. Interestingly, the smaller nanoparticles (synthesized by Synechococcus elongatus) were the most effective at removing Fe3+ and Mn2+ ions, probably due to their higher surface area:volume ratio. The green synthesized AgNPs proved to be an interesting system for the manufacture of biofilters that could be used to capture contaminant metals in water. [Display omitted] •Cyanobacteria and algae do eco-friendly green synthesis of metal nanoparticles.•Different silver NPs were synthesized by different species.•Nanobiofilters for metals remotion are of interest for water treatment.•AgNPs biosynthesized by microalgae and cyanobacteria can remove metals from water.